Use of Thoracoscopic Splanchnicectomy for the Relief of Chronic Pancreatic Pain: a Case Series - KB, Galketiya; V, Pinto; WRSM, Bandara (IIUM Medical Journal Malaysia, 2014)
Chronic pancreatitis may cause disabling pain not responding to oral analgesics and/or drainage procedures. Although pancreatectomy is a definitive treatment, it carries a significant morbidity and mortality. Celiac plexus ablation is beneficial, although it is a temporary method for pain relief. While bilateral splanchnicectomy provides a more permanent pain relief, it is a difficult procedure requiring thoracotomy and results in significant morbidity. Thoracoscopy is an attractive alternative to perform splanchnicectomy. The results of a case series on video assisted thoracoscopic sympathectomies performed at the university surgical unit, Peradeniya, Sri Lanka from January 2011 to June 2013 was analyzed to evaluate the surgical technique and to quantify the efficacy of pain relief. Operating time, blood loss, intraoperative complications, conversion to open surgery, pre-operative and post-operative pain assessment using visual analogue scale score (VAS) were recorded. Seven patients who underwent video assisted thoracoscopic splachnicectomy were analyzed. All had an acceptable operating time (6omin), no measurable blood loss, no conversions to open surgery, no intercostal drainage, early mobilization and feeding. All had an average VAS of 8-10 pre-operatively. This reduced to a VAS of 1 or no pain in all, on post-operative day one, at one and six months. The few who experienced mild pain needed occasional use of paracetamol or diclofenac sodium. Non required narcotic analgesics. Bilateral thoracoscopic splanchnicectomy is a safe, effective and more attractive alternative as it carries a minimum morbidity, mortality and provides an excellent relief of chronic agonizing pancreatic pain.